Simple solutions : - Schmitt, Thomas (John Wiley & Sons, 2007)
Despite the seemingly endless challenges and pressures in today's workplace, many people are firm in their resolve to assume leadership roles and make a difference. The problem? There simply isn't a clear-cut path to follow.